Current practice of neonatal resuscitation documentation in North America: a multi-center retrospective chart review. Issue 1 (December 2015) - Braga, Matthew; Kabbur, Prakash; Alur, Pradeep; Goodstein, Michael; Roberts, Kari; Satrom, Katie; Shivananda, Sandesh; Goswami, Ipsita; Pappagallo, Mariann; Briere, Carrie-Ellen; Suresh, Gautham
Abstract Background To determine the comprehensiveness of neonatal resuscitation documentation and to determine the association of various patient, provider and institutional factors with completeness of neonatal documentation. Methods Multi-center retrospective chart review of a sequential sample of very low birth weight infants born in 2013. The description of resuscitation in each infant's record was evaluated for the presence of 29 Resuscitation Data Items and assigned a Number of items documented per record. Covariates associated with this Assessment were identified. Results Charts of 263 infants were reviewed. The mean gestational age was 28.4 weeks, and the mean birth weight 1050 g. Of the infants, 69 % were singletons, and 74 % were delivered by Cesarean section. A mean of 13.2 (SD 3.5) of the 29 Resuscitation Data Items were registered for each birth. Items most frequently present were; review of obstetric history (98 %), Apgar scores (96 %), oxygen use (77 %), suctioning (71 %), and stimulation (62 %). In our model adjusted for measured covariates, the institution was significantly associated with documentation. Conclusions Neonatal resuscitation documentation is not standardized and has significant variation. Variation in documentation was mostly dependent on institutional factors, not infant or provider characteristics. Understanding this variation may lead to efforts to standardize documentation of neonatal resuscitation.